Exploring the co-infection of tuberculosis and hepatitis B virus in people living with HIV: Implications for diagnosis and treatment - Dansura, Mangpin L.; Dangana, Amos; Samuel, Bwede E.; Gagari, Villeng F.; Miri, Nanpon; Gyang, Nyiri M.; Adejuyigbe, Zacchaeus; Ugwu, Chinwe N.; Nanbol, Helen D.; Uzoebo, Nkiruka (School of Medicine, Universitas Syiah Kuala, 2024)
Hepatitis B virus (HBV) and tuberculosis (TB) infections are common causes of liver cirrhosis and hepatocellular carcinoma. First-line anti-TB medications are known to cause drug-induced liver injury (DILI). This study aimed to investigate whether HBV and TB co-infection increase susceptibility to liver failure and poor outcomes during anti-TB treatment in HIV-positive patients. HBV infection was detected using the ELISA method, while TB infection was confirmed through Lowenstein-Jensen (LJ) medium culture. The severity and incidence of liver failure and mortality were compared, and risk factors influencing clinical outcomes were identified. Patients were categorized as new TB cases, relapse TB cases, or defaulters. Among the total cases, 64.5% were classified as new, 18% as relapse, and 17.5% as defaulters TB cases. The prevalence of HBV infection among new, relapse, and defaulter cases was 11.5%, 4.8%, and 1.6%, respectively. In terms of TB classification, the prevalence of HBV infection among patients with pulmonary TB and extrapulmonary TB was 10.6% and 7.1%, respectively, with no cases recorded in the defaulter category. The prevalence of triple infection (HIV-TB-HBV) was found to be 13.3% in new TB cases and 3.3% in relapse TB cases. Patients undergoing anti-TB therapy with chronic HBV co-infection were more susceptible to liver failure and had poorer treatment outcomes. Regular monitoring of liver function is essential, and anti-HBV therapy should be considered for patients with high viral loads before initiating anti-TB treatment.